Prostate Cancer Screening among High-Risk Black Men - Roberts, Lisa R. (J Nurse Pract, 2018)
We explored potential barriers and facilitators for prostate cancer screening choices among high-risk Black men. In our sample of 264 Black men over 45 years of age living in the U.S. who met the American Cancer Society criteria for screening, we found that only 49.6% had ever been screened. We investigated potential barriers including screening intention, access to care, medical mistrust, and fatalism. Potential facilitating factors investigated were provider-patient conversations encompassing the pros and cons of screening, ethnicity taken into account, insurance, and previous prostate cancer screening. Recommendations and resources are suggested to increase screening of high-risk Black men.